Simple Pole Placement Controller for Elastic Joint Manipulator - Mohd Helmi, Suid; Mohd Zaidi, Mohd Tumari; Muhammad Salihin, Saealal; Yasmin, Abdul Wahab; Mohd Riduwan, Ghazali (2012)
This paper presents investigations into the development of simple pole placement controller for tip angular position tracking and deflection reduction of an elastic joint manipulator system. A Quanser elastic joint manipulator is considered and the dynamic model of the system is derived using the Euler-Lagrange formulation. The pole placement controller is designed based on integral state feedback structure and the feedback gain is computed based on the desired time response specifications of tip angular position. The proposed control scheme is also compared with a hybrid Linear Quadratic Regulator (LQR) with input shaper control scheme. The performances of the control schemes are assessed in terms of tip angular tracking capability, level of deflection angle reduction and time response specifications. Finally, a comparative assessment of the control techniques is presented and discussed.